ASSESSING YOGYAKARTA CREATIVE CITY ACCORDING TO CHARLES LANDRY’S CREATIVE CITY INDEX (The Indonesian Journal of Business Administration, 2019)
Indonesia has joined AEC (ASEAN Economic Community) that makes Indonesia has to compete internationally. Creative economic is believed to be one driving sector that can capture the opportunity of AEC. Therefore creativity and knowledge become an invaluable asset in competition and economic development. Indonesia try to increase competitiveness both in terms of products and human resources to be nation’s competitive advantage. The problems and challenges facing the national economy are also directly faced by the city of Yogyakarta. In the midst of effort to realize quality and sustainable economic development, Yogyakarta city is required to optimize the potential of human resource creativity. This research aims to know the readiness of Yogyakarta to sustainably the creative ecosytem in the city. The method that the researcher use is mixed method. This method combines qualitative and quantitative. The qualitative method used observation and interview to fifty respondents related to the topic and the quantitative method used survey research. This research founds that Yogyakarta has fulfilled seven indexes out of ten Charles Landry’s creative city index that are more than moderate level. The most subsector creative industry that influenced Yogyakarta are arts, performing arts, and music. These three top subsectors has already had its ecosystem. Yogyakarta can boost other indexes that is still in moderate level and build more facilitation to the top three subsectors.Keywords: Charles Landry, Creative City, Creative Economy, Creative Industry, Yogyakarta.